Pengaruh uang saku, teman sebaya dan pengelolaan keuangan terhadap pengeluaran keuangan siswa di SMAN 1 Anjir Pasar - Alfina Damayanti; Ananda Setiawan; Maulana Rizky; Monry Fraick Nicky Gillian Ratumbuysang (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This research aims to determine the influence of pocket money, peers and financial management on students' financial expenditure at SMAN 1 Anjir Pasar. The problem is focused on the relatively small amount of pocket money given to meet needs, peers influence spending and students do not have sufficient understanding of financial services so efforts are needed so that students are able to manage the money they earn well. The research method used is descriptive research with a quantitative approach. The sample was taken using a simple random sampling technique as many as 181 students of SMAN 1 Anjir Pasar. Data collection techniques are through questionnaires and observations of students as well as by taking references from journals, books and other relevant sources. This study used multiple regression with SPSS software to analyzed the research hyptoheses. The result indicates that all the predictor was not related with the dependent variable of the current research.